1998
DOI: 10.1007/s004300050071
|View full text |Cite
|
Sign up to set email alerts
|

Identification and localization of Chlamydia pneumoniae in the Alzheimer's brain

Abstract: We assessed whether the intracellular bacterium Chlamydia pneumoniae was present in post-mortem brain samples from patients with and without late-onset Alzheimer's disease (AD), since some indirect evidence seems to suggest that infection with the organism might be associated with the disease. Nucleic acids prepared from those samples were screened by polymerase chain reaction (PCR) assay for DNA sequences from the bacterium, and such analyses showed that brain areas with typical AD-related neuropathology were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
444
2
11

Year Published

1999
1999
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 447 publications
(469 citation statements)
references
References 92 publications
12
444
2
11
Order By: Relevance
“…Previous study of the relationship of C. pneumoniae and AD revealed genetic material from the organism in olfactory bulbs [16]. In addition, the organism was identified in the entorhinal cortex, the hippocampus, and the temporal cortex of AD brains suggesting that the organism can traffic to these sites [3]. Analogous to the human findings, infection was confirmed in the olfactory bulbs of our experimental mice indicating that the olfactory pathway is vulnerable to infection.…”
Section: Chlamydia Pneumoniae Infectionsupporting
confidence: 81%
See 4 more Smart Citations
“…Previous study of the relationship of C. pneumoniae and AD revealed genetic material from the organism in olfactory bulbs [16]. In addition, the organism was identified in the entorhinal cortex, the hippocampus, and the temporal cortex of AD brains suggesting that the organism can traffic to these sites [3]. Analogous to the human findings, infection was confirmed in the olfactory bulbs of our experimental mice indicating that the olfactory pathway is vulnerable to infection.…”
Section: Chlamydia Pneumoniae Infectionsupporting
confidence: 81%
“…Recent studies have shown that infection of monocytic cells enhances transmigration across a human brain microvascular endothelial cell layer [25]. Infected perivascular macrophages and monocytes have been observed in and around blood vessels in AD brains [3]. Taken together, these data suggest that infection of leukocytes with C. pneumoniae predisposes the central nervous system (human, and potentially mouse) to infection from the systemic circulation.…”
Section: Chlamydia Pneumoniae Infectionmentioning
confidence: 82%
See 3 more Smart Citations